Acute Effects of reducing vertical displacement and step frequency on running economy - Halvorsen, K.; Eriksson, M.; Gullstrand, L. (The Journal of Strength and Conditioning Research, 2012)
This work studies the immediate effects of altering the vertical displacement of the center of mass (VD) and step frequency (SF) on the metabolic cost of level treadmill running at 16 km/h on 16 male runners. Alterations of VD, SF, and the product VD × SF was induced using a novel feedback system, which presents target and current values to the runner by visual or auditory display. Target values were set to 5 and 10% reductions from individual baseline values. The results were expressed as relative changes from baseline values. Alterations led to an increase in metabolic cost in most cases, measured as VO2 uptake per minute and kilogram of body mass. Correlations were weak. Still, linear multiple regression revealed a positive coefficient (0.28) for the relationship between VD × SF and VO2. Separate rank correlation tests showed negative correlation (t = -0.19) between SF and VO2 and positive correlation (t = 0.16) between VD and VO2. There is a coupling between VD and SF caused by the mechanics of running; hence, isolated reduction of either factor was hard to achieve. The linear model also showed a negative coefficient for the relationship between the height of the center of mass above the ground (CoMh) and VO2. The effect size was small (multiple R2 0.07 and 0.12). Still the results indicate that reducing VD × SF by reducing the vertical displacement can have a positive effect on running economy, but a concurrent reduction in CoMh may diminish the positive effect. Midterm and long-term effects of altering the technique should also be studied.